SambaR: An R package for fast, easy and reproducible population‐genetic analyses of biallelic SNP data sets. (20th February 2021) - de Jong, Menno J.; de Jong, Joost F.; Hoelzel, A. Rus; Janke, Axel
Abstract: SNP data sets can be used to infer a wealth of information about natural populations, including information about their structure, genetic diversity, and the presence of loci under selection. However, SNP data analysis can be a time‐consuming and challenging process, not in the least because at present many different software packages are needed to execute and depict the wide variety of mainstream population‐genetic analyses. Here, we present SambaR, an integrative and user‐friendly R package which automates and simplifies quality control and population‐genetic analyses of biallelic SNP data sets. SambaR allows users to perform mainstream population‐genetic analyses and to generate a wide variety of ready to publish graphs with a minimum number of commands (less than 10). These wrapper commands call functions of existing packages (including adegenet, ape, LEA, poppr, pcadapt and StAMPP) as well as new tools uniquely implemented in SambaR. We tested SambaR on online available SNP data sets and found that SambaR can process data sets of over 100, 000 SNPs and hundreds of individuals within hours, given sufficient computing power. Newly developed tools implemented in SambaR facilitate optimization of filter settings, objective interpretation of ordination analyses, enhance comparability of diversity estimates from reduced representation library SNP data sets, and generate reduced SNP panels and structure‐like plots with Bayesian population assignment probabilities. SambaR facilitates rapid population genetic analyses on biallelic SNP data sets by removing three major time sinks: file handling, software learning, and data plotting. In addition, SambaR provides a convenient platform for SNP data storage and management, as well as several new utilities, including guidance in setting appropriate data filters. The SambaR source script, manual and example data set are distributed through GitHub: https://github.com/mennodejong1986/SambaR .